A visual analysis of English textbook “Pathway to English 3” used by Indonesian senior high schools - Anna Nuriskia; Sofyan A Gani; Saiful Marhaban (Universitas Syiah Kuala, 2021)
This paper focused on analysing the visual values found in the Pathway to English 3 textbook. In conducting this research, a descriptive qualitative approach was used. The content analysis model was applied. The data was taken from an English textbook published by Erlangga in 2015 entitled Pathway to English 3. A documentation approach was used to collect the data. The textbook was examined the data based on Kress and Leeuwen (2006) visual complementarity. There are three results of the research. First, most participants employed in Pathway to English 3 textbook are human participants (53.4%). Meanwhile, the non-human participants mostly used are object participants. Second, in terms of interactive meaning, the textbook supports the medium shot (69.5%) and the oblique perspective (54.9%). All of the pictures in the book are in black and white (100%). Additionally, (81.7%) images have a background. Last, from the compositional meaning, it was found that the images in the textbook are more presented to be informative (38.6%) rather than illustrative (34.8%) and decorative (26.6%). Furthermore, the dominant positions of the images are top/bottom position (60.7). In conclusion, textbook pictures can serve pedagogical purposes by supporting students in completing the tasks that follow the pictures.